Fractional polynomial response surface models - Gilmour, Steven G.; Trinca, Luiza A. [UNESP] (Springer Nature, 2005)
Second-order polynomial models have been used extensively to approximate the relationship between a response variable and several continuous factors. However, sometimes polynomial models do not adequately describe the important features of the response surface. This article describes the use of fractional polynomial models. It is shown how the models can be fitted, an appropriate model selected, and inference conducted. Polynomial and fractional polynomial models are fitted to two published datasets, illustrating that sometimes the fractional polynomial can give as good a fit to the data and much more plausible behavior between the design points than the polynomial model. © 2005 American Statistical Association and the International Biometric Society.
Keywords: Box-Tidwell transformations; Empirical modeling; Nonlinear regression; Parametric modeling; Response surface methodology; statistical analysis